2022
DOI: 10.1007/s00787-022-02032-4
|View full text |Cite
|
Sign up to set email alerts
|

Mental health burden of high school students, and suggestions for psychosocial support, 1.5 years into the COVID-19 pandemic in Austria

Abstract: The COVID-19 pandemic and containment efforts seem to be particularly challenging for adolescents. This study assessed mental health in high school students 1.5 years after the pandemic began in Austria. A cross-sectional survey was carried out from September to November 2021. Well-being (WHO-5), depressive symptoms, anxiety symptoms and sleep quality were assessed. A total of 1505 adolescents participated (78% girls). The cut-offs for clinically relevant symptoms were exceeded by 62% girls and 38.1% boys for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 54 publications
4
25
0
7
Order By: Relevance
“…The study is a snapshot between February and April 2021—that is, starting 2 weeks after the third lockdown ended—in Austria. Considering the results of Austrian data from other workgroups ( Pieh et al, 2020 , 2021 ; Dale et al, 2022 ), we fear a worsening of mental health (especially in girls) in the areas of well-being, depression, suicidal thoughts, and sleep, also after the end of our survey. In that same direction other groups report [ Özlü-Erkilic et al (2021) , here for Turkey and Austria in 15–25 year olds] that, as the pandemic progressed, the fear for themselves and/or a family member to become infected and/or ruminations about COVID-19 were steadily increasing from wave to wave.…”
Section: Discussionmentioning
confidence: 92%
“…The study is a snapshot between February and April 2021—that is, starting 2 weeks after the third lockdown ended—in Austria. Considering the results of Austrian data from other workgroups ( Pieh et al, 2020 , 2021 ; Dale et al, 2022 ), we fear a worsening of mental health (especially in girls) in the areas of well-being, depression, suicidal thoughts, and sleep, also after the end of our survey. In that same direction other groups report [ Özlü-Erkilic et al (2021) , here for Turkey and Austria in 15–25 year olds] that, as the pandemic progressed, the fear for themselves and/or a family member to become infected and/or ruminations about COVID-19 were steadily increasing from wave to wave.…”
Section: Discussionmentioning
confidence: 92%
“…A first follow-up study from 19 June to 2 July 2021, after one semester of distance learning, reported a slight improvement in mental health, albeit still at a lower level than before the pandemic [ 17 ]. This promising trend could not be replicated in a study from 14 September to 14 November 2021 [ 18 ]. Girls’ mental health had declined, while boys’ mental health remained at the same low levels as in February 2021.…”
Section: Introductionmentioning
confidence: 94%
“…Subjektives Bedrohungserleben und ökonomische Schwierigkeiten waren die besten Prädiktoren für eine verschlechterte psychische Gesundheit der Kin-review der [32]. Der psychischen Gesundheit der österreichischen Jugendlichen (mittleres Alter: 16,3 Jahre, Standardabweichung: 1,4 Jahre) nahmen sich Dale et al [5] an. Im September bis November 2021 wiesen 62 % der österreichischen Mädchen und 38 % der österreichischen Jungen klinisch relevante depressive Symptome auf.…”
Section: Verschlechterung Der Psychischen Gesundheit In Zeiten Der Co...unclassified
“…49 % der Mädchen und 29 % der Jungen hatten klinisch relevante Ängste und 28 % der Mädchen und 17 % der Jungen waren von Schlaflosigkeit betroffen. Die Prävalenz von Suizidgedanken innerhalb der letzten zwei Wochen betrug 47 % bei den Mädchen und 32 % bei den Jungen [5]. In einer "Gesund & Leben"-Umfrage mit österreichischen Schulärzt:innen gaben mehr als 81 % der Ärzt:innen an, dass sich der allgemeine Gesundheitszustand der Schüler:innen in der COVID-19 Pandemie verschlechtert hat.…”
Section: Verschlechterung Der Psychischen Gesundheit In Zeiten Der Co...unclassified